Microstructure and wear resistance of c-BN/Ni–Cr–Ti composites prepared by spark plasma sintering. (January 2016) - Wang, Y.; Lei, K.; Ruan, Y.; Dong, W.
Abstract: c-BN/Ni–Cr–Ti composites were fabricated by spark plasma sintering. The microstructure and the interfacial structure were analyzed by scanning electron microscopy, energy dispersive X-ray spectroscopy and X-ray diffraction analysis. The results show that the Ni–Cr–Ti alloy exhibits a good wettability to cover the c-BN particles. The interfacial bonding is strong and an interfacial reaction layer was found at the interface. The microscopic analysis revealed that Ti is the active element in the Ni–Cr–Ti alloy which is enriched in the c-BN particles and interacts with N and B, resulting in the formation of TiB2, TiB and TiN and promoting the chemical metallurgical bonding between the Ni–Cr–Ti alloy and c-BN. The non-smooth surface formed by the relative protrusion of the c-BN particles with their high hardness can resist the wear of the friction pairs during the wear experiments. The failure mode of the c-BN/Ni–Cr–Ti composites is fatigue shedding of the reinforcing hard phases of the c-BN particles as well as the micro-cutting and transfer of the Ni-based alloy surface. Highlights: There are dense interfacial bonding and reaction layer formed at the c-BN/Ni-Cr-Ti interface. The density of c-BN/Ni-Cr-Ti composites decreased slightly with an increase of c-BN content. The wear resistance of c-BN/Ni-Cr-Ti composites reached the highest at a c-BN content of 30 wt%. The failure mode of the composites is shedding of c-BN particles and micro-cutting and transfer of Ni-Cr-Ti alloy surface.